Middle School Mathematics Teachers' Perceptions of the Common Core State Standards for Mathematics and Related Assessment and Teacher Evaluation Systems. (March 2017) - Roth McDuffie, Amy; Drake, Corey; Choppin, Jeffrey; Davis, Jon D.; Magaña, Margarita V.; Carson, Cynthia
In this study, U.S. middle school teachers' perceptions of Common Core State Standards for Mathematics (CCSSM), CCSSM-related assessments, teacher evaluation processes, and resources for implementing CCSSM were investigated. Using a mixed methods design, a national sample of 366 teachers was surveyed, and 24 teachers were interviewed. Findings indicated that teachers viewed CCSSM as including new content for their grade level. Teachers also reported using multiple curriculum resources to align with CCSSM and indicated that new assessments would serve as a proxy for CCSSM. Implications for rapidly changing policy, curriculum, assessment, instruction, and professional development related to CCSSM are discussed.